Multidisciplinary Teleconsultation in Developing Countries (TELe-Health,, 2018)
This book presents a replicable model of multidisciplinary teleconsultation, designed and set up by Global Health Telemedicine, that offers very significant health benefits in remote and rural areas of developing countries. The model is based on experiences gained in sub-Saharan Africa while training and cooperating with local health professionals within the DREAM program, managed by the Community of Sant'Egidio. This program has to date treated almost 300,000 patients across many countries and has provided health education and disease prevention training to tens of millions. It originated in the context of the fight against AIDS but has been extended to encompass other pathologies and to exploit the capabilities of new telemedicine technologies that allow multispecialist teleconsultation (hence the acronym now represents "Disease Relief through Excellent and Advanced Means"). In addition to thorough description of the program, readers will find reflections and analysis on logistical, technical, sociological, and epidemiological issues. The book is divided into thematic chapters with easy-to-understand graphics. It will be a readily accessible source of information for professionals in international cooperation and global health students and professionals.